LITERATURE REVIEW : MANFAAT PIJAT PERINEUM UNTUK MENGURANGI RISIKO TERJADINYA LASERASI PERINEUM SAAT PERSALINAN - Ni Made Desi Dwijayani; Gusti Ayu Eka Utarini; Ni Wayan Suarniti (Universitas Aufa Royhan, 2026)
Perineal rupture is a common complication of vaginal delivery, especially in primiparas. It can occur spontaneously (laceration) or through an episiotomy. Prevention can be achieved through Kegel exercises, optimal holding positions, prenatal yoga, and perineal massage. Perineal massage is a technique used to massage the perineal area from the third trimester of pregnancy until several weeks before delivery to increase tissue elasticity. Perineal massage is believed to increase the elasticity of the perineal muscles and tissues, thereby minimizing trauma during childbirth.The purpose of this study was to analyze the effectiveness of perineal massage in reducing the risk and severity of perineal rupture. An electronic literature search was conducted in PubMed, Google Scholar, and Scopus for the period 2020–2025 using the keywords